RETRACTED: Organization of arrangement of permanent and temporary roads at construction sites to improve energy efficiency - Doroshin Ivan; Zhadanovsky Boris; Kazaryan Ruben (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 138, 00001 (2024), https://doi.org/10.1051/bioconf/202413800001